REPRESENTASI TOKOH PEREMPUAN DALAM FILM CINTA SUBUH KARYA ALI FARIGHI - Ma’arif, Moh. Syamsul; hikmah, miftahul (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to explain the depiction of women in the film 'Cinta Subuh' directed by Ali Farighi. There are many gender differences between men and women, including differences in status, roles, and responsibilities. This problem arises when women have limited opportunities compared to men who have extensive opportunities related to community programs and activities. This type of research is qualitative descriptive research. The data source is from the film "Cinta Subuh" directed by Ali Farighi. Research data collection techniques utilize listening and note-taking techniques. Data analysis techniques in this research include data collection, data reduction, data presentation, and concluding. An investigation into the depiction of female characters in the film 'Cinta Subuh' by Ali Farighi found 12 pieces of data.